A gradient engineered hole-transporting material for monolithic series-type large-area perovskite solar cells. Issue 40 (3rd August 2017) - Tu, Yongguang; Wu, Jihuai; He, Xin; Guo, Panfeng; Wu, Tongyue; Luo, Hui; Liu, Quanzhen; Wu, Qihui; Lin, Jianming; Huang, Miaoliang; Lan, Zhang; Li, Sizhong
Abstract : Further efficiency enhancement mainly relies on decreasing the interface losses between the active layers in perovskite solar cells. Abstract : Further efficiency enhancement mainly relies on decreasing the interface losses between the active layers in perovskite solar cells. The design of a gradient engineered hole-transporting material is expected to tune the interface losses in perovskite solar cells. In this work, we reported gradient engineering that afforded the hole-transport material (spiro-OMeTAD) dispersed in the upper part of the perovskite layer. Photoluminescence measurements indicated an enhanced hole extraction from the perovskite–spiro-OMeTAD gradient film. And a maximum PCE of 19.16% and a steady-state efficiency of 18.01% were obtained for the small-area device. Furthermore, we assembled monolithic series-type large-area perovskite solar cells based on gradient engineering. The large-area perovskite solar cell with an active area of 1.01 cm 2 obtained a PCE of 16.61%. Moreover, monolithic series-type large-area perovskite solar cells showed a V oc of 2.095 V for the binary module and a V oc of 3.104 V for the ternary module, respectively.